Performance, physiology, and determinants of success in IRONMAN® 70.3: A systematic review - Isabel von Känel-Cordoba; Matthias Wilhelm; Luciano Bernardes Leite; Marilia S. Andrade; Pantelis T. Nikolaidis; Pedro Forte; Daniela Chlibkova; Sasa Duric; Thomas Rosemann; Katja Weiss; Beat Knechtle (PLoS ONE, 2026)
Background IRONMAN® 70.3 events represent a rapidly expanding endurance discipline characterized by distinct physiological demands, performance determinants, and race-specific risk profiles. Despite their global popularity, no systematic review has synthesized evidence exclusively focused on this distance. Objective To consolidate current knowledge on performance predictors, physiological responses, training characteristics, nutritional strategies, environmental influences, and medical considerations in IRONMAN® 70.3 triathletes, and to identify gaps requiring further investigation. Methods A systematic search of PubMed, Scopus, SciELO, EBSCO and Google Scholar was conducted up to 25 th November 2025. Search terms were developed according to PRISMA guidelines and included variations of ‘Ironman 70.3’, ‘half triathlon’ and ‘middle-distance triathlon’. Eligible studies reporting physiological, anthropometric, nutritional, environmental, medical, or performance-related outcomes specific to IRONMAN® 70.3. Risk of bias was assessed using the Newcastle–Ottawa Scale, the Cochrane RoB tool, and the NIH Quality Assessment Tool, according to study design. Results A total of 86 studies were included, predominantly observational in design, with sample sizes ranging from 1 to 852,721 participants, mostly trained male triathletes aged 25–39 years. Participation has increased across age groups, with pronounced growth among female and masters triathletes. Peak performance in professional male triathletes is reached at approximately age 28, and in female triathletes at age 32. Across large datasets, cycling appeared to be the strongest predictor of overall race time, accounting for the largest proportion of performance variance. Physiologically, competition was associated with transient reductions in immune function, reversible muscle damage, and shifts in hydration and electrolyte balance, while higher intracellular water and efficient fat oxidation were associated with better outcomes. Conclusions Evidence specific to IRONMAN® 70.3 is limited by small sample sizes, heterogeneous designs, male-dominated cohorts, and insufficient sex-specific analyses. Future research should distinguish recreational from elite triathletes, incorporate balanced sex representation, and apply standardized physiological and environmental monitoring to refine targeted recommendations for performance, health, and safety.